Strategi Intensif Peningkatan Jumlah Konsumen untuk Mengembangkan Bisnis Food Court Koenyah - Amila Khairina (Ma'soem University, 2023)
Growth of food court is not as fast as other types of culinary sectors, while the number of SMEs in Bandung are keep growing. Koenyah Food Court as concept food court needs to capture that opportunity. Koenyah Food Court is a concept food court that gathers food from well-known street vendors and new culinary venture around Bandung in etalage. Koenyah Food Court’s growth is insignificant after running for one year since July 2016. Koenyah Food Court’s tenants interviewing is done to determine the root cause. The questions were made based on the fish bone analysis. After analyzing the answers from tenants, mostly they chose low number of consumers to be the most urgent issue that makes this insignificant growth happen. Several marketing tools such as Marketing Mix (7Ps), STP Analysis, Porter’s Five Forces, Competitor Analysis and Consumer Analysis is needed to help researcher determined their SWOT. After analyzing using TOWS matrix, the best improvement for Koenyah Food Court are expanded target market to the nearby area by proposed new STP, grab the potential experienced tenant, explore affordable but effective marketing activities, pricing strategy to attract new target market, keep the affordable price, comfortable place and good service of Koenyah Food Court.